Constructing a Stable and Efficient Buried Heterojunction via Halogen Bonding for Inverted Perovskite Solar Cells. Issue 2 (23rd November 2022) - Zhang, Caiyi; Shen, Xiangqian; Chen, Mengjiong; Zhao, Yan; Lin, Xuesong; Qin, Zhenzhen; Wang, Yanbo; Han, Liyuan
Abstract: The inverted perovskite solar cell has made great progress in recent years and the quality of the heterojunction has played a key role. Here, a series of halide‐substituted benzoic acid molecules are investigated as the bridge between nickel oxide and the perovskite, constructing a stable and efficient buried heterojunction via halogen bonding. The designed molecules are anchored at the surface of NiO by the coordination between the carboxyl and hydroxyl groups. On the opposite site of the molecules, strong halogen bonding is formed by binding the undercoordinated I − at the buried surface of the perovskite, which inhibits the generation of I2 under continuous light soaking and thereby suppresses the formation of voids. Moreover, the highly directional halogen bonding is beneficial for the oriented growth of perovskite crystals, which accelerate the carrier transport. As a result, the champion device yields a power conversion efficiency (PCE) of 22.02% and the encapsulated device maintains 91.86% of the initial PCE under continuous 1‐sun illumination at 55 °C for 1000 h. Abstract : 4‐iodo‐2, 3, 5, 6‐Tetrafluorobenzoic acid (I‐TFBA) with strong halogen bonding is introduced at the interface of NiO/perovskite. I‐TFBA is proven to effectively passivate the undercoordinated halide anions (I − ) traps to suppress I2 generation and induce oriented growth of the perovskite. As a result, the encapsulated champion device obtains a power conversion efficiency of 22.02% and maintains 91.86% of its initial value under 1000 h light soaking.